Enriched Expression and Developmental Regulation of the Middle-Weight Neurofilament (NF-M) Gene in Song Control Nuclei of the Zebra Finch - VELHO, TARCISO A.F. (2007)
Songbirds evolved a complex set of dimorphic telencephalic nuclei that are essential for the learning and production of song. These nuclei, which together make up the oscine song control system, present several neurochemical properties that distinguish them from the rest of the telencephalon. Here we show that the expression of the gene encoding the middle-weight neurofilament (NF-M), an important component of the neuronal cytoskeleton and a useful tool for studying the cytarchitectonic organization of mammalian cortical areas, is highly enriched in large neurons within pallial song control nuclei (nucleus HVC, robustus nucleus of the arcopallium, and lateral magnocellular nucleus of the nidopallium) of male zebra finches (Taeniopygia guttata). We also show that this transcript is highly expressed in large neurons in the medulla, pons, midbrain, and thalamus. Moreover, we demonstrate that NF-M expression in song control nuclei changes during postembryonic development, peaking during an early phase of the song-learning period that coincides with the maturation of the song system. We did not observe changes in NF-M expression in auditory areas or in song control nuclei in the contexts of hearing song or singing, although these contexts result in marked induction of the transcription factor ZENK. This observation suggests that NF-M might not be under the regulatory control of ZENK in auditory areas or in song control nuclei. Overall, our data indicate that NF-M is a neurochemical marker for pallial song control nuclei and provide suggestive evidence of an involvement of NF-M in the development and/or maturation of the oscine song control system.